Occupational exposure to anesthetics leads to genomic instability, cytotoxicity and proliferative changes - Souza, Kátina M. [UNESP]; Braz, Leandro Gobbo [UNESP]; Nogueira, Flávia R. [UNESP]; Souza, Marajane B. [UNESP]; Bincoleto, Lahis F. [UNESP]; Aun, Aline G. [UNESP]; Corrente, José E. [UNESP]; Carvalho, Lídia R. [UNESP]; Braz, José Reinaldo C. [UNESP]; Braz, Mariana Gobbo [UNESP] (Elsevier, 2016)
Data on the genotoxic and mutagenic effects of occupational exposure to the most frequently used volatile anesthetics are limited and controversial. The current study is the first to evaluate genomic instability, cell death and proliferative index in exfoliated buccal cells (EBC) from anesthesiologists. We also evaluated DNA damage and determined the concentrations of the anesthetic gases most commonly used in operating rooms. This study was conducted on physicians who were allocated into two groups: the exposed group, which consisted of anesthesiologists who had been exposed to waste anesthetic gases (isoflurane, sevoflurane, desflurane and nitrous oxide − N2O) for at least two years; and the control group, which consisted of non-exposed physicians matched for age, sex and lifestyle with the exposed group. Venous blood and EBC samples were collected from all participants. Basal DNA damage was evaluated in lymphocytes by the comet assay, whereas the buccal micronucleus (MN) cytome (BMCyt) assay was applied to evaluate genotoxic and cytotoxic effects. The concentrations of N2O and anesthetics were measured via a portable infrared spectrophotometer. The average concentration of waste gases was greater than 5 parts per million (ppm) for all of the halogenated anesthetics and was more than 170 ppm for N2O, expressed as a time-weighted average. There was no significant difference between the groups in relation to lymphocyte DNA damage. The exposed group had higher frequencies of MN, karyorrhexis and pyknosis, and a lower frequency of basal cells compared with the control group. In conclusion, exposure to modern waste anesthetic gases did not induce systemic DNA damage, but it did result in genomic instability, cytotoxicity and proliferative changes, which were detected in the EBC of anesthesiologists. Thus, these professionals can be considered at risk for developing genetic alterations resulting from occupational exposure to these gases, suggesting the need to minimize this exposure.
Keywords: Anesthetic gases; Comet assay; Environmental air pollutants; Genomic instability; Micronucleus assay; Occupational exposure